Manufacture of a novel anisotropic bacterial nanocellulose hydrogel membrane by using a rotary drum bioreactor. (1st May 2019) - Chen, Genqiang; Chen, Lin; Wang, Wei; Hong, Feng F.; Zhu, Meifang
Graphical abstract: Highlights: Anisotropic BNC hydrogel membranes are first produced using a rotary drum bioreactor. BNC membranes possessed anisotropic morphology and anisotropic tensile properties. BNC possessed sparse network, high light transmittance and ultrahigh water content. Hydrogel productivity in the rotary drum culture was 3.73 times of the static culture. Light transmittance was bigger though thickness of BNC from rotary drum bioreactor was higher than from tray. Abstract: Since anisotropic hydrogel membranes have great potential in tissue engineering and bioseparation, the aim of this study was to produce an anisotropic BNC hydrogel membrane for the first time with enhanced BNC productivity by using a newly designed 30-L horizontal rotary drum bioreactor. As compared with the traditional tray static cultivation, the BNC hydrogel from the rotary drum bioreactor showed anisotropic morphology, sparser network, lower dry matter content of 0.16 w/w%, thicker fiber diameter, and lower degree of polymerization that was still 1.8 times higher than cotton, and featured with much higher ultraviolet-visible light transmittance, as well as demonstrated anisotropic tensile properties, lower Young's modulus of 0.23 MPa and compressive modulus of 0.99 kPa. The productivity of dry and wet BNC was enhanced by 1.65 times and 3.73 times, respectively. The proposed technology may not only obtain anisotropic BNC hydrogel membranes with high transparency, but also promote the BNC productivity.